MORPHOLOGICAL AND ANALYTIC CAUSATIVE CONSTRUCTION IN DELI JAVANESE DIALECT - Zuindra Zuindra; Mulyadi Mulyadi (Universitas Islam Sumatera Utara (UISU), 2020)
This article discusses causative construction of Deli Javanese dialect which focuses on morphological and analytic causative construction. This study aims to reveal how morphological and analytic causative constructions in Deli Javanese dialect are formed. The theory of causative construction concept is based on Comrie (1989). The research data were obtained from text books, journals and interview. The causative construction in this analysis was elaborated by using tree diagram. The result showed that the morphological causative construction of Deli Javanese dialect utilized the verbs, which were shown by prefixes and suffixes. The causative construction in the verb nggodoke ‘boil something for somebody’ is derived from nggodok ‘boil’; thus, it is indicated by the suffix –e. Meanwhile, the analytic causative construction utilized nggawe ‘make’ in which it indicates an action with desire. Furthermore, Analytic causative construction in Deli Javanese dialect is a clause construction, which has two predicates. This research finally provides some contributions and references for any further research related to the causative construction within any languages.